Reframing Musical Expressivity: Cognitive, Relational, and Pedagogical Dimensions - Setyawan, Dedi (Indonesian Scientific Publication, 2024)
This narrative review explores the determinants of musical expressivity in performance, focusing on attentional focus, accompaniment quality, and mindfulness-based strategies as critical factors influencing perception and evaluation. The study aimed to synthesize empirical findings across music psychology, pedagogy, and performance studies to develop an integrative understanding of expressivity. Literature was collected systematically through Scopus, Web of Science, and Google Scholar, using targeted keyword combinations and applying rigorous inclusion and exclusion criteria. The review incorporated diverse methodologies, including experimental, cohort, and case study designs, to capture the multidimensional nature of expressivity.Results revealed that attentional focus significantly shapes audience evaluations, demonstrating that perception is mediated by cognitive framing and cultural orientation. Accompaniment quality was shown to enhance interpretive cohesion, emphasizing the relational dimension of performance. Additionally, mindfulness practices improved expressive depth by helping musicians manage stress and sustain emotional engagement, yielding benefits for both performers and audiences. Discussion highlighted systemic barriers such as narrow pedagogical frameworks and biased evaluative practices that undermine expressive development. Potential solutions include embedding mindfulness programs, fostering collaborative rehearsal strategies, and integrating attentional framing into curricula. The findings affirm the urgency of reconceptualizing expressivity as a central component of music education and performance evaluation. Future research should expand beyond Western classical contexts, adopt multimodal approaches, and address structural barriers to expressive development. By advancing these perspectives, this review contributes to a holistic understanding of musical expressivity and its vital role in creating meaningful and resonant performance experiences.